Ground Penetrating Radar's (GPR) imaging and applications to pavement structural assessment: a case of Malaysia - Muslim, N. H. (Warsaw University of Technology, 2017)
Traditionally, pavement distress evaluations were carried out by visual observation. Traditional practice requires a person to walk along the stretch of the pavement to conduct distress survey, take photo and measure defects occurred at deteriorated surfaces. However, this approach is too subjective, generates inconsistencies of information, less reliable and time-consuming. Due to these shortcomings, the transportation practitioners in pavement maintenance seek for other alternative tools and techniques to arrest incapability of traditional practices. One of the tools available in the market is Ground Penetrating Radar (GPR). GPR is a geophysical tool known by ability to accommodate extensive data in pavement assessment, geotechnical investigation and structural assessment. The application of GPR is such new to most of road maintenance industry in Malaysia. Therefore, this study has been undertaken to evaluate the benefits of using GPR imaging and its application in assessing pavement structures in Malaysia. The GPR survey was conducted in Meranti street located at UTM (Universiti Teknologi Malaysia) campus, and then analyzed using REFLEX 2D simulation software. The finding shows there are three (3) types of information obtained from GPR survey included; identification of raw image and processed image, identification of pavement segments thickness, and identification of GPR response towards surface and subsurface conditions, which illustrated in radargram images. Furthermore, the GPR can perform at high speed and can save time. It is also beneficial for long-term investment due to ability to provide extensive information at a greater depth. The research indicates that interpretation of GPR's radargram images consumes time due to the low resolution. Therefore, selection of GPR system is subject to level of accuracy and clarity of radar images needed in a project.